1980
DOI: 10.1111/j.1432-1033.1980.tb04991.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Characteristics of the Trinucleoside Diphosphate dApdApdA and Its Constituents from Nuclear Magnetic Resonance and Circular Dichroism Studies

Abstract: Proton NMR studies at 360 MHz were carried out on the trinucleoside diphosphate dApdApdA, the dinucleoside monophosphate dApdA and the methylphosphate esters of the monomers pdA, pdAp and dAp. The compounds were also investigated by means of circular dichroism at varying temperatures. Complete NM R spectral assignments are given. The thermodynamics of stacking derived from the circular dichroic spectra was used to extrapolate the observed coupling constants, measured at a range of temperatures, to values appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Furthermore, the detailed geometry of the S-type sugar rings appears to undergo a shift when another A residue stacks on top of a given nucleotide unit [7]. The NMR results are summarized in Table 1.…”
Section: Chain-length Dqwndencementioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, the detailed geometry of the S-type sugar rings appears to undergo a shift when another A residue stacks on top of a given nucleotide unit [7]. The NMR results are summarized in Table 1.…”
Section: Chain-length Dqwndencementioning
confidence: 93%
“…Indeed, without the aid of this vital piece of information the present analysis would not have been feasible. In short, our NMR study [7] showed conclusively that all residues in the fully stacked right-handed (dA),, single helix adopt a B-DNA-like geometry, except the final pdA unit, which still possesses two conformational degrees of freedom. It is well known [29] that the €3-DNA genus of geometries (B, C, D-DNA) displays a single outstanding common feature, i.e.…”
Section: Chain-length Dqwndencementioning
confidence: 95%
See 3 more Smart Citations